2020
DOI: 10.1007/s13595-020-00978-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of fertilization on stone pine growth and cone production

Abstract: & Key message Fertilization is a feasible management technique for Pinus pinea L. cropping, with increased cone production up to 9 years after the application and superior trunk diameter growth every year. Fertilization effects on cone size-weight indicate the value of re-fertilizing. & Context Stone pine (Pinus pinea) is a species of economic interest for its highly in demand pine nuts. Despite the high value of pine nuts, cones are harvested mostly from non-managed forests. Consequently, advances in cropping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The effect of fertilization on diameter growth was previously reported for horticultural crops (Brun and Tournier 1992) and stone pine (Loewe-Muñoz et al 2020). Measuring short-term stem diameter changes and coupling them to environmental conditions is a practical approach to the understanding of stem sensitivity to management interventions and of the species-specific patterns (McMahon and Parker 2015;Cocozza et al 2018;Zalloni et al 2018).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The effect of fertilization on diameter growth was previously reported for horticultural crops (Brun and Tournier 1992) and stone pine (Loewe-Muñoz et al 2020). Measuring short-term stem diameter changes and coupling them to environmental conditions is a practical approach to the understanding of stem sensitivity to management interventions and of the species-specific patterns (McMahon and Parker 2015;Cocozza et al 2018;Zalloni et al 2018).…”
Section: Introductionmentioning
confidence: 91%
“…The species is sensitive to deficiency of micronutrients such as boron (Bento and Coutinho 2011) and iron (Malchi and Shenker 2011). Diameter growth was found to be stimulated by fertilization (Loewe-Muñoz et al 2020); this effect is important due to the correlation between diameter at breast height (DBH, 1.3 m) and cone production (Freire et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This longitudinal multi-environment study showed the dependence of PY on cone weight; hence, management practices, such as fertilization and irrigation, could be used to boost production of heavy cones. In fact, previous studies reported that fertilization increased PY [61] and cone weight [62,63]. The benefits of fertilization with both micronutrients [64,65] and macronutrients [21,38] have been studied in adult stone pine trees.…”
Section: Plos Onementioning
confidence: 99%